Optimal carbon pricing in general equilibrium: temperature caps and stranded assets in an extended annual DSGE model - Van Der Ploeg, F; Rezai, A (University of Oxford, 2021)
The general equilibrium model developed by Golosov et al. (2014), GHKT for short, is modified to allow for additional negative impacts of global warming on utility and productivity growth, mean reversion in the ratio of climate damages to production, labour-augmenting technical progress, and population growth. We also replace the GHKT assumption of full depreciation of capital each decade by annual logarithmic depreciation. Furthermore, we allow the government to use a lower discount rate than the private sector. We derive a tractable rule for the optimal carbon price for each of these extensions. We then simplify the GHKT model by modelling temperature as cumulative emissions and calibrating it to Burke et al. (2015) damages. Finally, we consider how the rule for the optimal carbon price must be modified to allow for a temperature cap, and what this implies for stranded oil and gas reserves. We illustrate our analytical results with a range of optimal policy simulations.